Diagnostic value of ROC curve evaluation of serum markers in acute cholecystitis with bacterial infection - Li, Duo; Yue, Zhu; Weng, Yibing; Zhen, Genshen (Journal of the Pakistan Medical Association, 2022)
Objective: To explore correlation of serum markers human neutrophil lipocalin and C-reactive protein with acute cholecystitis associated with bacterial infection, and to evaluate the diagnostic value of the markers. Method: The cross-sectional study was conducted from January 2018 to April 2020 at the Beijing Luhe Hospital, Capital Medical University, Beijing, China, and comprised acute cholecystitis patients who were divided into bacterial infection group A and non-bacterial infection group B. Serum human neutrophil lipocalin and C-reactive protein were measured for both the groups. Receiver operating characteristic curve was used to evaluate the diagnostic value of the two markers in acute cholecystitis associated with bacterial infection. Data was analysed using SPSS 25. Results: Of the 145 patients, 65(45%) were in group A; 36(55.38%) males and 29(44.62%) females with a mean age of 45.79±2.50 years. In group B there were 80(55%) subjects; 45(56.25%) males and 35(43.75%) females with a mean age of 46.16±2.52 years (p>0.05). In group A, there were 60(92.31%) cases of acute calculous cholecystitis, and 5(7.69%) had acute acalculous cholecystitis compared to 73(91.25%) and 7(8.75%), respectively, in group B (p>0.05). Serum human neutrophil lipocalin and C-reactive protein levels in group A were higher than group B (p<0.001). Serum human neutrophil lipocalin showed a high positive correlation with C-reactive protein in group A (r=0.800, p<0.001), and a moderate positive correlation in group B (r=0.683, p<0.001). Area under the curve of serum human neutrophil lipocalin associated with C-reactive protein was 0.901 ---Continue